Courage and Career Construction by Young Adults: The Mediating Effect of Promotional and Preventive Self-Regulation - Paszkowska-Rogacz, Anna (Przegląd Psychologiczny, 2025)
Aim: The aim of the study was to determine the relationship between courage and four key components of the career construction process among young adults: (a) crystallisation of self-image as an employee, (b) exploration of career fields, (c) career decision-making, and (d) preparation for job performance. The study also aimed to evaluate the mediating role of promotional and preventive self-regulation in these relationships. Methods: The study included a total of 300 young adults (158 women and 142 men) aged between 18 and 29 years (M = 25.14, SD = 3.11). All completed the Student Career Construction Inventory (SCCI), Courage Questionnaire and the Promotion and Prevention Self-Regulation Scale (PPSS). Results: A strong positive relationship was observed between courage and the four components of the career construction. Promotional self-regulation was found to mediate all the studied relationships; however, preventive self-regulation did not demonstrate any mediating effect regarding crystallisation of self-image as an employee. Conclusion: Our findings suggest that courage can be interpreted as an adaptive behaviour that supports coping with career development tasks and adapting to changing conditions associated with work and working life. Furthermore, both achievement- and aspiration-focused, and duty- and security-focused, self-regulatory systems were shown to mediate the relationship between courage and the multidimensional process of career construction, albeit to varying degrees.